Quantifying the association between bovine and human trypanosomiasis in newly affected sleeping sickness areas of Uganda. - Beatrix von Wissmann; Jenna Fyfe; Kim Picozzi; Louise Hamill; Charles Waiswa; Susan C Welburn (Public Library of Science (PLoS), 2014)
BACKGROUND: Uganda has active foci of both chronic and acute HAT with the acute zoonotic form of disease classically considered to be restricted to southeast Uganda, while the focus of the chronic form of HAT was confined to the northwest of the country. Acute HAT has however been migrating from its traditional disease focus, spreading rapidly to new districts, a spread linked to movement of infected cattle following restocking. Cattle act as long-term reservoirs of human infective T. b. rhodesiense showing few signs of morbidity, yet posing a significant risk to human health. It is important to understand the relationship between infected cattle and infected individuals so that an appropriate response can be made to the risk posed to the community from animals infected with human pathogens in a village setting. METHODOLOGY/PRINCIPAL FINDINGS: This paper examines the relationship between human T. b. rhodesiense infection and human infective and non-human T. brucei s.l. circulating in cattle at village level in Kaberamaido and Dokolo Districts, Uganda. The study was undertaken in villages that had reported a case of sleeping sickness in the six months prior to sample collection and those villages that had never reported a case of sleeping sickness. CONCLUSIONS AND SIGNIFICANCE: The sleeping sickness status of the villages had a significant effect with higher odds of infection in cattle from case than from non-case villages for T. brucei s.l. (OR: 2.94, 95%CI: 1.38-6.24). Cattle age had a significant effect (p<0.001) on the likelihood of T. brucei s.l. infection within cattle: cattle between 18-36 months (OR: 3.51, 95%CI: 1.63-7.51) and cattle over 36 months (OR: 4.20, 95%CI: 2.08-8.67) had significantly higher odds of T. brucei s. l. infection than cattle under 18 months of age. Furthermore, village human sleeping sickness status had a significant effect (p<0.05) on the detection of T. b. rhodesiense in the village cattle herd, with significantly higher likelihood of T. b. rhodesiense in the village cattle of case villages (OR: 25, 95%CI: 1.2-520.71). Overall a higher than average T. brucei s.l. prevalence (>16.3%) in a village herd over was associated with significantly higher likelihood of T. b. rhodesiense being detected in a herd (OR: 25, 95%CI: 1.2-520.71).